Decompressive craniectomy for severe middle cerebral artery infarction: a meta-analysis of randomised controlled trials. (October 2016) - Li, Yuping; Hou, Mengzhuo; Lu, Guangyu; Ciccone, Natalia; Dong, Lun; Yan, Zhengcun; Cheng, Chen; Wang, Xingdong; Zhang, Hengzhu
Abstract: Background: Severe middle cerebral artery infarction is defined as an acute infarction in the entire middle cerebral artery territory. Several case series have indicated that decompressive hemicraniectomy for severe middle cerebral artery infarction is lifesaving. However, data concerning the long-term functional outcome are insufficient. We did a systematic review and meta-analysis to assess the efficacy of decompressive hemicraniectomy for patients with severe middle cerebral artery infarction. Methods: According to PRISMA guidelines, we searched databases containing articles published in English (MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials CENTRAL) and Chinese (Chinese Biomedical Literature Database, China Science and Technology Journal Database, and China National Knowledge Infrastructure) for randomised controlled trials (RCTs) of decompressive hemicraniectomy published before January, 2016. We extracted data on patient characteristics, methodological quality, and outcome measures. The outcomes assessed included mortality and good functional outcome (GFO). We did a subgroup analysis to determine the effect of age and surgical timing on mortality and functional outcomes. Findings: 14 studies were included in this meta-analysis, including 830 patients with severe middle cerebral artery infarction. In the total population, mortality was lower in the decompressive hemicraniectomy group than in the conventional treatment group at 6 months after onset (odds ratio [OR] 0·19, 95% CI 0·11–0·33; p<0·0001), and at 12 months (OR 0·18, 0·11–0·28; p<0·0001). The pooled OR of GFO was 3·15 (95% CI 1·49–6·69; p=0·003) at 6 months, and 1·95 (1·19–3·19; p=0·008) at 12 months. Survival with moderately severe disability was higher in the decompressive hemicraniectomy group at 6 months (OR 3·90, 95% CI 2·23–6·83; p<0·0001) and 12 months (OR 4·36, 2·55–7·36; p<0·0001). However, with regard to survival with severe disability, no significant differences were observed (p=0·55 at 6 months, p=0·81 at 12 months). In the subgroup analysis, compared with conventional treatment, decompressive hemicraniectomy significantly decreased mortality in patients older than 60 years (p<0·0001) and 60 years or younger (p<0·0001). With regard to survival with moderately severe or severe disability, significant differences were observed between treatment groups both in patients older than 60 years (p=0·0002) and 60 years or younger (p=0·0002). No significant differences between treatment groups were found in the subgroup analysis of surgical timing. Interpretation: Compared with conventional treatment, decompressive hemicraniectomy could significantly reduce mortality and improve prognosis both in patients older than 60 years and those aged 60 years or younger with severe middle cerebral artery infarction. However, compared with conventional treatment, more patients who receive decompressive hemicraniectomy might survive with moderately severe or severe disability. Funding: None.